2004
DOI: 10.1021/jm049924d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Potent Dipeptidyl Peptidase IV Inhibitors with Enhanced Chemical Stability:  Interplay between the N-Terminal Amino Acid Alkyl Side Chain and the Cyclopropyl Group of α-Aminoacyl-l-cis-4,5-methanoprolinenitrile-Based Inhibitors

Abstract: A series of methanoprolinenitrile-containing dipeptide mimetics were synthesized and assayed as inhibitors of the N-terminal sequence-specific serine protease dipeptidyl peptidase IV (DPP-IV). The catalytic action of DPP-IV is the principle means of degradation of glucagon-like peptide-1, a key mediator of glucose-stimulated insulin secretion, and DPP-IV inhibition shows clinical benefit as a novel mechanism for treatment of type 2 diabetes. However, many of the reversible inhibitors to date suffer from chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 68 publications
0
57
0
Order By: Relevance
“…This was confirmed in a study using another strain of rats (Vancouver diabetic fatty rats) in which 12 weeks treatment with P32/98 increased both hepatic and peripheral insulin sensitivity as determined by euglycemic hyperinsulinemic clamp with tracer glucose infusion [101]. Glucose tolerance and insulin secretion after oral glucose have also been shown to be augmented by oral administration of two methanoprolinenitrile dipeptidederived DPP-4 inhibitors in obese Zucker rats [92] as well as after oral administration of the DPP-4-inhibitor, LAF237, in normal and insulin resistant mice [102]. Hence, several studies have demonstrated that pharmacological DPP-4 inhibitors improve glucose tolerance in both normal animals and in different animal models of glucose intolerance or diabetes and that this is executed in association with increased concentration of active GLP-1 and insulin.…”
Section: Dpp-4 Inhibition In Animal Studiesmentioning
confidence: 73%
See 1 more Smart Citation
“…This was confirmed in a study using another strain of rats (Vancouver diabetic fatty rats) in which 12 weeks treatment with P32/98 increased both hepatic and peripheral insulin sensitivity as determined by euglycemic hyperinsulinemic clamp with tracer glucose infusion [101]. Glucose tolerance and insulin secretion after oral glucose have also been shown to be augmented by oral administration of two methanoprolinenitrile dipeptidederived DPP-4 inhibitors in obese Zucker rats [92] as well as after oral administration of the DPP-4-inhibitor, LAF237, in normal and insulin resistant mice [102]. Hence, several studies have demonstrated that pharmacological DPP-4 inhibitors improve glucose tolerance in both normal animals and in different animal models of glucose intolerance or diabetes and that this is executed in association with increased concentration of active GLP-1 and insulin.…”
Section: Dpp-4 Inhibition In Animal Studiesmentioning
confidence: 73%
“…Also N-alkylamines based on cyanopyrrolidine have been shown to have great chemical stability [90,91] and recently it was also reported that dipeptide surrogate compounds containing a cyclopropanated prolinenitrile derived from proline are potent DPP-4 inhibitors with high chemical stability [92]. Therefore, there exists today a number of stable DPP-4 inhibitors being reversible inhibitors of the catalytic site of DPP-4.…”
Section: Pharmacological Dpp-4 Inhibitorsmentioning
confidence: 99%
“…189 (Figure 61) It was proposed that the locking of the cyanopyrrolidine into a stable trans-rotameric conformation would enhance favorable, directed binding within the active site of DPP-IV, and preclude the inactivating intramolecular cyclization reaction. 189 To substantiate this hypothesis, Magnin and coworkers 189 introduced the cis-4,5-methano (fused cyclopropyl ring) across the C4 and C5 of the cyanopyrroldine P1 moiety and in a separate communication, 187 Augeri and coworkers introduced the sterically demanding adamantyl P2 moiety on the N-terminus, leading to the discovery of compound 147. (Figure 61, left panel) Both the steric bulk at P2 and the sterically constrained cyclopropane fused pyrrolidine P1 moiety cooperatively contributed towards enhancing the trans-rotameric conformational stability and in vitro potency of 147.…”
Section: Dipeptidylpeptidase-iv (Dpp-iv) Inhibitor 147 (Saxagliptin/omentioning
confidence: 99%
“…3 A systemic study to improve the chemical stability of such nitrile-containing compounds has been reported recently. 4 Inhibitors lacking an electrophile, such as 3 and 4, are generally of only modest intrinsic potency. 5 Earlier reports from our laboratories described 4-amino cyclohexylglycine analogues 5 and 6 as potent DP-IV inhibitors lacking an electrophile.…”
mentioning
confidence: 99%